Rhizosphere microbial characteristics of pioneer plant Oxyria sinensis Hemsl. in abandoned Pb-Zn mining area - Tang, Hong; Yang, Jie; Yuan, Xin-qi; Wang, Si-chen; Li, Lin-yang; Duan, Chang-qun (Frontiers in Ecology and Evolution, 2023)
Oxyria sinensis has the characteristics of drought resistance, barren resistance, pollution resistance and clonal reproduction, and has the potential to be developed as a restoration plant ( pioneer plant ) for vegetation restoration and heavy metal pollution control in mining wasteland. In this study, the rhizosphere microbial communities of the pioneer plant O. sinensis growing in a lead-zinc mine wasteland and the rhizosphere microbial communities of O. sinensis growing in adjacent non-mining areas were studied by field investigation. There were significant differences in the composition of microbial communities between the rhizosphere soil of O. sinensis and the bare soil. There were significant differences in the composition of soil microbial communities between the non-mining area control and the lead-zinc mine wasteland. Compared with the non-mining area control, the rhizosphere soil of O. sinensis in the lead-zinc mine wasteland had a unique microbial community. The dominant bacteria were Nitrospirae, Chloroflexi, Proteobacteria, Actinobacteria, Ascomycota and Kickxellomycota. Further gene function prediction showed that the metabolic pathway sequences related to heavy metal ion transport, heavy metal resistance and repair in the rhizosphere soil of O. sinensis were more abundant than those in the control. The dominant ecological functional groups of fungi in the rhizosphere soil of O. sinensis were saprophytic flora and pathological flora. Plenodomus, Surfurifusis, Sphingomonas, Filobasidium and Articulospora were enriched in the rhizosphere soil of O. sinensis in the abandoned land of lead-zinc mining area, and had high tolerance to heavy metals in the soil, indicating that O. sinensis can recruit heavy metal-tolerant microbial groups to promote its survival and adaptation in the abandoned land of the mining area.